Association between γ′ fibrinogen levels and inflammation - Alexander, Kristine S.; Madden, Theresa E.; Farrell, David H. (Thrombosis and Haemostasis, 2011)
The γ’ fibrinogen isoform produces clots that are stiffer and more resistant to breakdown than the more common fibrinogen isoform, γA. Increased levels of γ’ fibrinogen are associated with several forms of cardiovascular disease. The purpose of this cross-sectional study was to investigate the relationship between γ’ fibrinogen, an emerging risk factor for cardiovascular disease, and inflammatory markers in subjects with a chronic inflammatory state. The 284 subjects for this study came from the Periodontitis And Vascular Events (PAVE) study, and γ’ fibrinogen and total fibrinogen in plasma were measured by ELISA. Information on patient demographics and health status, as well as levels of C-reactive protein (CRP), an inflammatory marker, have previously been collected for this study. The mean (SE) γ’ fibrinogen level in the subjects was 0.622 (0.017) mg/ml. Levels of γ’ fibrinogen were correlated with CRP (p = 0.006), with a one unit increase in CRP associated with a 1.9% increase in γ’ fibrinogen, after adjustment for potential confounders. Total fibrinogen was not correlated with γ’ fibrinogen in these subjects. The number of dental sites with evidence of tissue inflammation was also significantly associated with γ’ fibrinogen levels. These results provide an important step in the evolution of γ’ fibrinogen not only as a general risk factor for cardiovascular disease, but as a potentially useful biomarker for assessing a patient’s inflammatory state and associated cardiovascular disease risk.
Keywords: Cardiovascular disease; γ’ fibrinogen; inflammation; periodontitis; risk factor